Garbage Sorting as an Important Rural Problem: Descriptive Study of Priority Health Problems in Pantai Cermin Village, Langkat Regency - Rapotan Hasibuan; Atikah Salsabila (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
In planning efforts to improve public health degrees, it is necessary to plan the first steps to find out what health problems are prioritized to be addressed effectively, efficiently, and on target. This community service, therefore, aim to to find health problems in order to find the right intervention so that the health problems contained in Teladan Hamlet do not become serious problems that cause other health problems. This research was conducted in Teladan hamlet of Pantai Cermin Village, Tanjung Pura Subdistrict using descriptive research methods, univariate analysis was conducted to determine the priority of health problems from the results of self-aware surveys. Prioritization of health problems was carried out qualitatively using the Focus Group Discussion method with USG (Urgency, Seriousness, Growth) criteria scoring. The nine highest health problems found were the low number of couples who did not use contraception, low infant weight, itching, hypertension, national health insurance, smoking behavior, kitchen waste disposal, garbage sorting, and eradication of mosquito nests. The results of the Focus Group Discussion agreed that the priority of health problems in Teladan hamlet is the low behavior of waste sorting, so that interventions are carried out in the form of counseling and provision of facilities and infrastructure in the form of garbage cans in some public places in order to increase public knowledge and community behavior in sorting waste. Efforts that can be made by local governments are to support and supervise the community to implement good and correct waste sorting and processing behavior in a sustainable manner